A resource-driven acquisition by a Chinese firm - Wu, Xiaobo (Henry Stewart Talks, 2017)
This case study considers Fulida’s acquisition of Neucel to emphasise the importance of resource-driven acquisitions. Faced with increased demand and a reduction in Chinese cotton output, Fulida sought to increase the supply of raw materials needed to manufacture viscose fibre. Fulida decided to acquire Nuecel, one of the largest global wood pulp suppliers.